Effects of Family Income and Maternal Education on the Risk of Low Birth Weight - Maryana, Dyan; Murti, Bhisma; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2024)
Background: LBW babies are still a problem, especially in developing countries. Family income and maternal education are factors that influence health service outcomes, including preventing low birth weight babies. The aim of this study was to analyze the influence of family income and maternal education on the risk of low birth weight babies. Subject and Methods: Observational analytical research design with a cross sectional approach. The sampling technique is random sampling. The research was conducted in Blora Regency, Central Java with a sample size of 200 mothers with newborn babies. The dependent variable is low birth weight. The independent variables consist of exposure to cigarette smoke, maternal age, family income, pos pelayanan terpadu strata and maternal education. The study instrument used was a questionnaire. Data were analyzed using path analysis with STATA 13. Result: The results of the path analysis explain that the risk of low birth weight babies is directly influenced by family income and this influence is statistically significant. Pregnant women with high family income have a risk of giving birth to babies with low birth weight 0.5 times compared to low family income (OR= 0.52; 95% CI= 0.27 to 1.00; p= 0.050). There was no significant effect of pos pelayanan terpadu strata or exposure to cigarette smoke on the risk of babies with low birth weight (LBW). Family income is influenced by the mother's education and this influence is statistically significant. The higher the mother's education, the higher the family income (OR= 2.35; 95% CI= 1.32 to 4.21; p = 0.004). There is a relationship between maternal age and maternal education and this relationship is statistically significant. Older mothers on average had lower education (OR= 0.43; 95% CI= 0.24 to 0.77; p = 0.004). Conclusion: There is a direct influence between family income, pos pelayanan terpadu strata and exposure to cigarette smoke on the risk of LBW babies. There is an indirect effect between maternal education on family income, and maternal age on maternal education.